The beloved hope chest - Clipston, Amy (Clipston, Amy. Amish heirloom novel, 2017)
"In the final installment of the Amish Heirloom series, the Fisher sisters learn the mystery behind their parents' marriage--and about the sibling who has never been spoken of. Mattie Fisher's three daughters know that she's been keeping a secret from them. With each item pulled from the beloved family hope chest, they've discovered a new clue about their mother's past. But there's a reason Mattie has been keeping her history hidden, and she's not sure she's ready to reopen old wounds. Will dredging up the past change the way her children view her? Or her marriage to their father? And can she handle the pain of revisiting the memories that preceded the last few happy decades? Mattie's story is one of grief and learning to love again. But like the best things preserved in a hope chest, it's a story of love and redemption born out of heartache--and it's past time to share it"--